Prevalence of anemia and its associated factors among female university students in Jashore, Bangladesh - Farjana Fardaus; Md. Nowshad Mahmud Choyon; Md. Sakhawot Hossain; Md. Obydullah; Farjana Khatun; Md. Hasibul Hasan Milton; Fakir Md. Shah Hafiz; Tanvir Ahmad (Discover Public Health)
Abstract Background Anemia is a prevalent public health issue globally, particularly in developing countries, and significantly affects women of reproductive age in Bangladesh. This study examines the prevalence and associated factors of anemia among female students at Jashore University of Science and Technology, Bangladesh. Methods A cross-sectional study was conducted from November 2023 to March 2024 among 401 randomly selected female students (18–28 years) at Jashore University of Science and Technology who did not report any known chronic illnesses or visible signs of acute illness at the time of data collection. A multi-stage sampling method was used. First, students were divided into two strata—those living in halls and those living off-campus—to compare the effect of institutional diet on anemia. Then, simple random sampling was applied within each stratum. Data on socio-demographics, anthropometry, clinical status, and dietary intake were collected through interviewer-administered structured questionnaires and direct measurements. Hemoglobin levels were assessed to determine anemia status. Statistical analysis was performed using SPSS (version 26), applying chi-square tests and binary logistic regression. Results Among the 401 participants, 42.9% (n = 172) were anemic, of whom 60.5% (n = 104) had mild anemia, 36.6% (n = 63) had moderate anemia, and 2.9% (n = 5) had severe anemia. Anemia was significantly more prevalent among individuals from lower-income households (10,000–25,000 BDT) [OR = 4.19, 95% CI: 1.92–9.15, p < 0.001] and those residing instudent halls [OR = 5.02, 95% CI: 1.28–19.76, p = 0.021]. Participants with low red meat consumption had notably higher odds of anemia [OR = 15.48, 95% CI: 3.01–79.54, p = 0.001]. A positive family history of anemia [OR = 8.93, 95% CI: 1.40–55.05, p = 0.021] and consuming tea or coffee soon after meals [OR = 5.79, 95% CI: 2.21–11.79, p = 0.001] were also identified as significant associated factors. Conclusion Anemia affected a substantial proportion of the study population, with significant associations observed for low family income, residential status, infrequent red meat consumption, family history of anemia, and improper timing of tea/coffee intake. These findings highlight the critical need for targeted dietary interventions and comprehensive awareness programs to reduce anemia prevalence among female university students.